동물모델에서 柴胡加龍骨牡蠣湯의 수면유도 및 항불안 효과 - 임준식(Junsik Lim); 임강현(Kanghyun Leem); 김태연(Taeyeon Kim) (동의생리병리학회지, 2021)
Shihogayonggolmoryo-tang (ST) is a Korean medical herb cocktail which has been used to treat anxiety induced insomnia. In this study, we will examine sleep-promoting and anti-anxiety effects of ST, and investigate its mechanism. ICR mice were divided into three groups for the first examination : control group (n=11), ST50 group (50 mg/kg, po, n=11), ST200 group (200 mg/kg, po, n=11). Sleep-promoting effect was confirmed by measuring the sleeping duration time and sleeping onset time after thiopental sodium treatment (50 mg/kg, ip). ICR mice were divided into five groups for the second examination : control group (n=11), ST200 group (200 mg/kg, po, n=11), ST200+Flumazenil group (ST 200 mg/kg, po, flumazenil 0.3 mg/kg, ip, n=11), diazepam group (1 mg/kg, ip, n=11), diazepam+flumazenil group (diazepam 1 mg/kg, ip, Flumazenil 0.3 mg/kg, ip, n=11). Anxiety behavior and sleep-promoting effect was confirmed by open field test and measuring the sleeping duration time and sleeping onset time. Expression levels of c-fos in tuberomammillary nucleus (TMN) and ventrolateral preoptic nucleus (VLPO) were analyzed by immunohistochemistry. ST treated group showed significantly decreased anxiety behavior and enhanced sleeping duration time and sleeping onset time concentration dependently. The expression of c-fos was significantly upregulated in VLPO as sleep-inducing center and TMN as downregulated in arousal center by ST treatment. In addition, all effects of ST were reversed by flumazenil. Our results suggest that ST has sleep-promoting and anti-anxiety effects through regulating arousal center (TMN) and sleep-inducing center (VLPO). KCI Citation Count: 0